[bmim]BF4-accelarated One-pot Synthesis of 2-amino Thiazole Derivatives - Duc, Dau X.; Chung, Nguyen Thi (Letters in Organic Chemistry, 2023)
An efficient and environmentally-friendly protocol for the synthesis of 2- (arylamino) thiazoles has been investigated. The two-step, three-component reaction of aryl ketones, Nbromosuccinimide, and thiourea derivatives was performed using [bmim][BF4] ionic liquid as a solvent in one pot and gave products in good to excellent yields. Furthermore, the ionic liquid could be reused up to the 5th time without a considerable decrease in the reaction yield. Thirteen thiazoles were obtained in high yields (78-89%) under mild conditions (ambient temperature and relatively short reaction time) and their structures were confirmed by NMR data.
Keywords: thioureas